Quantitative analysis of the influence of asymmetric channel delay on relay protection's reliability - Huisheng GAO; Qing SHEN (Dianxin kexue)
The asymmetric delay of digital channels has negative effects on line current differential protection in a complex mechanism. Hence, it's necessary to use effective methods to improve the reliability of relay protection. Firstly, the operation principle and criterion of line current differential protection were analyzed.Then, the influence of asymmetric delay on the reliability of relay protection was analyzed, and the quantitative analysis method of the influence under different fault conditions was determined. Finally, the feasibility and correctness of the method were verified. The results show that effects of asymmetric delay on reliability of relay protection have a significant correlation with fault conditions. This conclusion has practical value in reliability evaluation and channel optimization of relay protection.